Matrushka Immigration Abuse Lack of Education Negative Familial Factors and Juvenile Delinquency - Tütüncüler, Akın; Karagöz, Y Mustafa; Demirçin, Sema; Atılgan, Mehmet (The Bulletin of Legal Medicine, 2008)
The past history of immigration and exposition to abuse has negative effects on childhood crime. Especially immigration due to economical reasons may lead to familial anger and violence and abused child by the other members of the family. In this study a face to face questionnaire was performed to 1163 children who were claimed to commit or participate in a crime and were sent to Antalya Forensic Medicine Office for examination. The questionnaire included questions about age, gender, education, attributed and previous crimes they committed, immigration, physical abuse history, work, family size, number of brother/sister, room number of house in which they are living and size of family member they are sharing the bedroom. The data obtained from results were evaluated in the light of related references.Key words: Immigration, childhood delinquency, child abuse
Keywords: immigration; childhood delinquency; child abuse